ANALYSIS OF MONTHLY SHIPPING TURNOVER TARGET AT PT GLOBAL JET EXPRES MEDAN PERJUANGAN BRANCH, MEDAN ROUTE BASED ON OPERATIONAL COSTS - Putri Anggita Berutu; Dwi Oktavia Teresa; Naftalia Napitupulu; Delima Hutabarat; Hamonangan Siallagan (RADJA PUBLIKA, 2025)
Turnover is an important indicator in measuring business performance in various sectors, especially in assessing business growth, formulating strategies, and making financial decisions. In addition, turnover also reflects market conditions, financial stability, and the company's level of profit through the amount of income earned. Therefore, setting turnover targets periodically is an essential strategic step in business management. One method that can be used to determine monthly turnover targets is the Break Even Point (BEP) approach. This method helps business actors, especially in the service sector, in calculating turnover targets based on fixed cost calculations and contribution margins or Variable Cost. Determining turnover targets without considering these two components can pose a risk of loss, especially for freight forwarding companies that are the object of study in this article.